Endoplasmic reticulum stress sensitizes cells to DNA damage-induced apoptosis through p53-dependent suppression of p21(CDKN1A) - Mlynarczyk, Coraline; Fåhraeus, Robin (Nature communications, 2014)
Endoplasmic reticulum (ER) stress occurs in poorly perfused tissues and activates the p53 isoform p53/47 to promote G2 arrest via 14-3-3σ. This contrasts with the p21(CDKN1A)-dependent G1 arrest caused by p53 following DNA damage. It is not known how cells respond to conditions when both pathways are activated. Here we show that p53/47 prevents p53-induced p21 transcription during ER stress and that both isoforms repress p21 mRNA translation. This prevents p21 from promoting COP1-mediated 14-3-3σ degradation and leads to G2 arrest. DNA damage does not result in p53-dependent induction of p21 during ER stress and instead results in an increase in p53-induced apoptosis. This illustrates how p53 isoforms target an intrinsic balance between the G1 and G2 checkpoints for cell cycle coordination and demonstrates an ER stress-dependent p53 pathway that suppresses p21 and lowers the apoptotic threshold to genotoxic drugs.
Keywords: ubikvitinligasy; HCT116 buňky; MFC-7 buňky; Humans; Cell Cycle Checkpoints; Biomarkers, Tumor; nádorový supresorový protein p53; kontrolní body fáze G2 buněčného cyklu; lidé; Ubiquitin-Protein Ligases; exoribonukleasy; proteiny 14-3-3; apoptóza; nádorové biomarkery; Cyclin-Dependent Kinase Inhibitor p21; stres endoplazmatického retikula; Endoplasmic Reticulum Stress; 14-3-3 Proteins; kontrolní body buněčného cyklu; nádorové buněčné linie; poškození DNA; DNA Damage; HCT116 Cells; Cell Line, Tumor; Exoribonucleases; inhibitor p21 cyklin-dependentní kinasy; Apoptosis; G2 Phase Cell Cycle Checkpoints; MCF-7 Cells; Tumor Suppressor Protein p53